Digitainability and open innovation: how they change innovation processes and strategies in the agrifood sector? - Piot-Lepetit, Isabelle (Frontiers in Sustainable Food Systems, 2023)
By developing a conceptual analysis, this research explores the possibility of fostering a convergence between digitalization and sustainability, also named digitainability. This convergence is often seen as an opportunity to solve the various challenges the agrifood sector faces nowadays, especially those of feeding more people without deteriorating the environment and creating social divides and, at the same time, managing specific risks related to climate change, biodiversity loss, and hunger. The research describes how open innovation is becoming an imperative and explains the contribution of startups in the development of these new innovative initiatives. It also explains how sustainability considerations are closely linked to the development of servitization in the business context. Finally, it explores how these changes impact established companies, forcing them to develop ambidextrous innovation strategies to maintain and support their competitive advantage. In doing so, the paper illustrates some of the well-known effects of this ongoing change, while identifying the opportunities created and the challenges for which more research is still needed.